Mapping the conceptual structure of intellectual capital research: A co-word analysis - Omid Faraji; Kaveh Asiaei; Zabihollah Rezaee; Nick Bontis; Ehsan Dolatzarei (Journal of Innovation & Knowledge (JIK), 2022)
This bibliometric study aims to map the conceptual structure of intellectual capital (IC) research between 1975 and 2020 using co-word analysis and social network analysis drawing upon the Web of Science database. The results show that 12,310 documents have been published from 1975 to 2020. From a total of 6,516 keywords used in documents, the five most frequent keywords have been identified as: 'performance', 'innovation', 'knowledge', 'impact', and 'management'. The United States is the top-producing country with 3,303 documents. In addition, the findings indicate that the Journal of Intellectual Capital is the most prolific journal with 208 articles, and the Academy of Management Journal is the most frequently cited journal with 11,914 citations. The National Bureau of Economic Research (NBER) is the world's most prolific research institute with 84 documents. The most frequently used keywords in different geographical regions show that except for South America, where the most frequently used keyword is 'innovation', 'performance' is the most common keyword in Asia, Europe, North America, Oceania, and Africa. This study provides a comprehensive picture of the current state of IC research, thereby paving the way for future studies by shedding light on the gaps in the literature and presenting suggestions for future research.
Keywords: 650; Co-word analysis; Intellectual capital; Scientific map; Social network analysis; Web of Science database